Differential equations for engineers and scientists - Cengel, Yunus A. (McGraw Hill, 2013)
Differential Equations for Engineers and Scientists is intended to be used in a first course on differential equations taken by science and engineering students. It covers the standard topics on differential equations with a wealth of applications drawn from engineering and science--with more engineering-specific examples than any other similar text. The text is the outcome of the lecture notes developed by the authors over the years in teaching differential equations to engineering students. Like Yunus Cengel's other texts, the material is introduced at a level that a typical student can follow comfortably, and the authors have made the text speak to the students and not over them. Differential Equations for Engineers and Scientists is written in plain language to help students learn the material without being hampered by excessive rigor or jargon. The friendly tone and the logical order are designed to motivate the student to read the book with interest and enthusiasm.